2023
DOI: 10.3389/fpls.2023.1247600
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of zinc foliar sprays for wheat grain biofortification: a review of current applications and future perspectives

José Tonatiuh Sánchez-Palacios,
David Henry,
Beth Penrose
et al.

Abstract: Agronomic biofortification of wheat grain with zinc can improve the condition of about one billion people suffering from zinc (Zn) deficiency. However, with the challenge of cultivating high-yielding wheat varieties in Zn-deficient soils and the global need to produce higher-quality food that nourishes the growing population, innovation in the strategies to deliver Zn directly to plants will come into play. Consequently, existing foliar formulations will need further refinement to maintain the high agronomic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…In foliar spray, ZnO-NPs are applied to the leaf surface and then they are absorbed by leaf cuticle and stomata. As a result, nanoparticles are transported within the plants through phloem sieve tubes [ 62 ]. For instance, Zhu et al [ 63 ] reported that ZnO-NPs penetrate the leaf epidermis through stomata, accumulate in the plastid, and translocate into chloroplasts.…”
Section: Mechanisms Of Zinc Nanoparticles’ Uptake and Transport In Pl...mentioning
confidence: 99%
“…In foliar spray, ZnO-NPs are applied to the leaf surface and then they are absorbed by leaf cuticle and stomata. As a result, nanoparticles are transported within the plants through phloem sieve tubes [ 62 ]. For instance, Zhu et al [ 63 ] reported that ZnO-NPs penetrate the leaf epidermis through stomata, accumulate in the plastid, and translocate into chloroplasts.…”
Section: Mechanisms Of Zinc Nanoparticles’ Uptake and Transport In Pl...mentioning
confidence: 99%
“…In the case of foliar application, ZnO nanoparticles are sprayed onto the leaf surface and can be absorbed through the stomata and cuticle (Figure 2A). Subsequently, they are further transported within the plant through phloem sieve tubes, facilitating their wholeplant conduction [125]. Zhu et al demonstrated that ZnO nanoparticles can penetrate the epidermis through stomata, accumulate in plastid exosomes, and then translocate to chloroplasts [65].…”
Section: Absorption and Transfer Of Zno Nanoparticles In The Plantmentioning
confidence: 99%
“…In addition to being a major source of starch and energy, it also provides proteins, vitamins, dietary fibers, and phytochemicals . The yield and quality of wheat are greatly dependent on chemical fertilizers, and nitrogen (N) and potassium (K) play an important role in improving the wheat yield and quality. As an essential micronutrient, zinc (Zn) application in wheat, especially foliar spraying, effectively alleviates zinc deficiency in humans. However, current agricultural practices have focused on the long-term application of chemical fertilizers, which while effective has also created problems in the soil environment. Improving wheat yield by changing the plant microbiome to improve its nutrient uptake and resistance to pathogens is of great significance for the sustainable development of an intensive agricultural ecosystem. …”
Section: Introductionmentioning
confidence: 99%